Late Complication of Laparoscopic Sleeve Gastrectomy - Anthony Dakwar; Ahmad Assalia; Iyad Khamaysi; Yoram Kluger; Ahmad Mahajna (Case Reports in Gastrointestinal Medicine)
Laparoscopic sleeve gastrectomy (LSG) is gaining popularity for the treatment of morbid obesity. It is a simple, low-cost procedure resulting in significant weight loss within a short period of time. LSG is a safe procedure with a low complication rate. The complications encountered nevertheless can result in morbidity and even mortality. The most significant complications are staple-line bleeding, stricture, and staple-line leak. The purpose of this paper is to present a patient who suffered from a staple-line leak presenting 16 months after LSG. Review of the current literature regarding this complication as well as outline of a strategy for the management of post-LSG gastric leaks is suggested.